Adenosine and Prostaglandin E2 Production by Human Inducible Regulatory T Cells in Health and Disease - Whiteside, Theresa L.; Jackson, Edwin K. (Frontiers in Immunology, 2013)
Regulatory T cells (Treg) play a key role in maintaining the balance of immune responses in human health and in disease. Treg come in many flavors and can utilize a variety of mechanisms to modulate immune responses. In cancer, inducible (i) or adaptive Treg expand, accumulate in tissues and peripheral blood of patients and represent a functionally-prominent component of CD4+ T lymphocytes. Phenotypically and functionally, iTreg are distinct from natural (n) Treg. A subset of iTreg expressing ectonucleotidases CD39 and CD73 is able to hydrolyze ATP to 5’-AMP and adenosine (ADO) and thus mediate suppression of those immune cells which express ADO receptors. iTeg can also produce prostaglandin E2 (PGE2). The mechanisms responsible for iTeg-mediated suppression involve binding of ADO and PGE2 produced by iTreg to their respective receptors expressed on Teff, leading to the up-regulation of adenylate cyclase and cAMP activities in Teff and to their functional inhibition. The potential for regulating these mechanisms by the use of pharmacologic inhibitors to relieve iTreg-mediated suppression in cancer suggests the development of therapeutic strategies targeting the ADO and PGE2 pathways.